Acute and subacute effects of the selective serotonin-noradrenaline reuptake inhibitor duloxetine on cardiac hERG channels - Fischer, Fathima; Vonderlin, Nadine; Seyler, Claudia; Zitron, Edgar; Schernus, B.; Katus, Hugo; Scholz, Eberhard P. (Naunyn-Schmiedeberg's archives of pharmacology, 2013)
Duloxetine is a selective serotonin-noradrenaline reuptake inhibitor approved for treatment of major depressive disorder. So far, duloxetine has been found to be well tolerated and reported cardiac side effects were negligible. However, pharmacological effects on cardiac hERG channels have not been properly addressed yet. hERG channels were expressed in Xenopus oocytes and a human embryonic kidney (HEK) cell line. Currents were measured using voltage clamp and patch clamp techniques. Channel surface expression was quantified using Western blot analysis. We found that duloxetine inhibits heterologously expressed hERG channels in a concentration-dependent manner, yielding an IC50 of 142.8 μM in Xenopus oocytes. Inhibitory effects were even more pronounced when using a mammalian cell line resulting in a 34 or 59 % current decrease by 10 or 30 μM duloxetine, respectively. Duloxetine did not affect channel activation or inactivation kinetics. However, channel deactivation was accelerated by duloxetine. We further showed that inhibition occurs in the open and inactivated, but not closed, states. There was no frequency dependence of block. However, effects of duloxetine were significantly attenuated when using the hERG pore mutants Y652A and F656A. Subacute effects of duloxetine on hERG channel expression were analyzed using the Western blot technique. We found that incubation with duloxetine results in a concentration-dependent decrease of channel surface expression. Whereas inhibitory effects of duloxetine seem negligible under therapeutically relevant concentrations, hERG block should be considered in cases of duloxetine overdose and when administering duloxetine to patients susceptible to drug-induced QT prolongation.
Gesehen am 06.04.2021